Multi-layer Pavement System under Blast Load - Wu, Jun.; Wu, Hao.; Tan, Hong Wei Andy.; Chew, Soon Hoe.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book proposes the concept of a multi-layer pavement system to fulfill the blast resistance requirement for pavement design. It also presents a damage pattern chart for multi-layer pavement design and rapid repair after blast load. Such a multi-layer system consists of three layers including asphalt concrete (AC) reinforced with Geogrid (GST) at the top, a high-strength concrete (HSC) layer in the middle, and engineered cementitious composites (ECC) at the bottom. A series of large-scale laboratory impact tests were carried out to prove the usefulness of this concept and show its advantages over other conventional pavement system. Furthermore, field blast tests were conducted to show the actual behavior of this multi-layer pavement system subjected to blast load under real-world conditions.
Keywords: Civil engineering; Building materials; Mechanics, Applied; Solids; Computer simulation; Ceramic materials; Transportation engineering; Traffic engineering; Civil Engineering; Structural Materials; Solid Mechanics; Computer Modelling; Ceramics; Transportation Technology and Traffic Engineering